Rough Sets, Fuzzy Sets, Data Mining and Granular Computing 13th International Conference, RSFDGrC 2011, Moscow, Russia, June 25-27, 2011. Proceedings - Kuznetsov, Sergei O.; Slezak, Dominik; Hepting, Daryl H.; Mirkin, Boris G. (Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 13th International Conference on Rough Sets, Fuzzy Sets, Data Mining, and Granular Computing, RSFDGrC 2011, held in Moscow, Russia in June 2011. The 49 revised full papers presented together with 5 invited and 2 tutorial papers were carefully reviewed and selected from a total of 83 submissions. The papers are organized in topical sections on rough sets and approximations, coverings and granules, fuzzy set models, fuzzy set applications, compound values, feature seletion and reduction, clusters and concepts, rules and trees, image processing, and interactions and visualization.